Assessing Corporate Culture of an Enterprise-based on Competing Values Framework Design - BALANDINA, Iryna S.; OBOLENTSEVA, Larysa V.; ALEKSANDROVA, Svitlana A.; POLYAKOVA, Yana O.; DULFAN, Sergii B. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The corporate culture of the enterprise in the present conditions becomes an effective competitive advantage, the uniqueness of which is to exclude the possibility of copying it by other market participants through the reproduction of the process of social interaction between the employees of the company on the basis of the formed common ideas and understanding. Therefore, the main purpose of the work is to assess the corporate culture of the enterprise based on competing values framework design. The state enterprise ‘Plant for chemical reagents’ (SC ‘Zavod khimichnykh reaktyviv’) was chosen as the research object. An important step in assessing the corporate culture, for the period under study, is the analysis of the internal labor resources of the enterprise. It was established that the research object reduced the number of staff members. The work revealed vectors of corporate culture. It was also found that the company is recommended to introduce a new information system, taking into account the need for market monitoring; to improve the system of motivation of employees of the enterprise; complete the certification process according to ISO 2010 standards.